Economic Psychology and the Value Problem - Knight, Frank H. (Quarterly Journal of Economics, 1925)
The basic difficulty in economic theory is the philosophical problem of the meaning of explanation in connection with human behavior. I. Motive or desire in human conduct is the analogue of force in mechanics, 375. II. Is force real or merely symbolic, leaving movement (behavior in the case of human beings) the only fact open to description or study? 379. — This question is merely formal in physics, for we know forces by their effects alone, and hence unambiguously if at all; but in the realm of conduct, we know motives in ourselves directly and in others by communication, in addition to inferring them from observed behavior, and the two sources of information disagree considerably. III–IV. The intellectually embarrassing but unescapable fact of purposiveness, in thought as well as conduct, 386. — V. The place of motives and their treatment in economics, which has to be critical as well as descriptive and logical, — a branch of esthetics and ethics as well as of science, 400. — VI. The objective of economic activity and the point of view of social criticism of the economic order, 406.